Analysis of the Relationship between Hemodynamic Status, Age, and Body Mass Index on Postural Balance in Patients with a History of Chronic Disease - Ni Luh Ayu Putu Indah Yulantari; I Ketut Arya Yoga Krismantara; Aryaning Dwi Antyesti; I Gusti Putu Martha Kusuma (PT Inovasi Pratama Internasional, 2026)
Background: Postural balance is a crucial motor component in maintaining functional stability. A decline in postural control performance significantly increases the risk of falls, particularly among populations with chronic comorbidities and degenerative conditions.Objective: This study aims to analyze the functional health profile and examine the correlation between hemodynamic status, age, and Body Mass Index (BMI) toward postural balance performance in patients with a history of chronic diseases.Methods: This quantitative study used a cross-sectional design utilizing secondary data from a community health screening initiative (n = 13). Parameters evaluated included demographic characteristics (age and sex), hemodynamic status (systolic/diastolic blood pressure and heart rate), anthropometry (BMI), and functional postural balance score (P. Balance). Data were analyzed using descriptive statistics and Pearson correlation coefficients (r) via Python programming. Results: The majority of respondents were female (92.3%) with a mean age of 53.15 ± 13.02 years old. The average functional balance score of the subjects was 2.23 ± 0.60. Correlation analysis revealed that Systolic Blood Pressure (SBP) demonstrated the strongest moderate negative correlation with functional balance performance (r = -0.45). Conversely, age (r = -0.16) and BMI (r = 0.11) exhibited weak correlations with the subjects' postural stability.Conclusion: Hemodynamic status, particularly systolic blood pressure, carries a more substantial functional relationship with postural control stability compared to age and anthropometric factors among populations with chronic comorbidities. Future community health interventions are recommended to prioritize hypertension management combined with targeted balance strategy training.